2016
DOI: 10.1002/per.2050
|View full text |Cite
|
Sign up to set email alerts
|

Recalling an Attachment Event Moderates Distress after Ostracism

Abstract: Ostracism is known to cause psychological distress. Studies have indicated that immediate distress is resistant to individual differences and situational factors, but delayed reactions are more sensitive to moderation. Because attachment orientation is inextricably tied to rejection and inclusion, we hypothesized that attachment orientation would moderate both immediate and delayed ostracism effects and that recalling an attachment event compatible with a person's attachment internal working model would modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 77 publications
(112 reference statements)
6
28
2
Order By: Relevance
“…The findings also extend previous work on the moderating role of attachment orientations on ostracism (Arriaga et al, 2014;Yaakobi & Williams, 2016a, 2016b. This may suggest that the denial and suppression explanation could underlie the effects for anxious individuals found here.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The findings also extend previous work on the moderating role of attachment orientations on ostracism (Arriaga et al, 2014;Yaakobi & Williams, 2016a, 2016b. This may suggest that the denial and suppression explanation could underlie the effects for anxious individuals found here.…”
Section: Discussionsupporting
confidence: 87%
“…Attachment anxiety was also associated with low needs satisfaction in a sample of highly committed couples (Arriaga et al, 2014) when either ostracized or included. Moreover, avoidant and anxious attachment moderated these ostracism effects in two diverse cultures (Yaakobi & Williams, 2016a, 2016b. In a different study, attachment anxiety and avoidance were shown to moderate the negative effects of ostracism; specifically, recalling an attachment event that was consistent with one's attachment internal working model moderated the negative effects of ostracism and led to less reduction in participants' needs satisfaction after being ostracized (Yaakobi & Williams, 2016b).…”
Section: Attachment Theory and Researchmentioning
confidence: 89%
See 3 more Smart Citations